Equality of Rights and Accessibility Policy Interventions as Prevention of Sexual Violence against Persons with Disabilities: A Mixed Method Study - ., Suardi; ., Nursalam; Nur , Rahmat; Nur , Hasruddin (Journal of Ecohumanism, 2024)
The primary issue in this study is the pervasive sexual abuse directed at students with disabilities at Indonesian colleges. This study aims to examine initiatives aimed at preventing sexual violence against students by evaluating Equality of rights and accessibility policies for individuals with disabilities in Indonesian universities. This research employs a combination of qualitative and quantitative methodologies. The research involved 30 informants selected through purposive sampling, comprising members of the Campus Honorary and Ethics Council, the Task Force Prevention and Handling of Sexual Violence (PHSV), sociologists, legal experts, lecturers, and students. Additionally, 677 respondents were chosen using random sampling techniques for the research sample. The data collection methods include distributing questionnaires, conducting observations, performing interviews, and reviewing paperwork. The stages of reduction, presentation, and conclusion are qualitative data analysis, whereas quantitative data analysis employed descriptive statistics utilizing JASP 0.19.0 software. The results of the study show that structural intervention through Equality of rights and accessibility policies for people with disabilities is an important thing to be done by university leaders, such as the provision of courses or seminars with a disability perspective, reporting services or channels, prevention guidelines, coordination mechanisms between units, socialization of anti-sexual violence, decent accommodation and sexual violence ambassadors. Intervention in the policy structure of Equality of rights and accessibility measures for individuals with impairments can mitigate sexual abuse against students with disabilities.